Regulasi Metode Pembayaran Dengan Mata Uang Kripto (Cryptocurrency) Dalam Transaksi Bisnis Internasional - Razaq Mustika Djati; Tjokorda Istri Diah Widyantari Pradnya Dewi (CV. Lenggogeni Data Publishing, 2024)
This research is normative research using a statutory regulation approach, a concept approach, and a comparative approach. The law used consists of primary legal materials, namely regulations and international agreements and publications of international organizations, as well as secondary legal materials obtained from relevant books, journals, literature, documents, and archives through library research. The results of this research show that, (1) due to the absence of official regulations that prohibit cryptocurrency transactions and coupled with several regulations regarding international electronic transactions that can also be applied to these transactions, this transaction is permitted to be carried out as long as the country where the transaction is carried out allows it or holds bilateral agreements with other countries regarding this regulation. (2) Cryptocurrency transactions give rise to various legal problems, especially legal threats in international trade law; these legal threats are more accurately described as disclosures of laws or statutory regulations. There are several multilateral efforts by countries to establish arrangements or regulations for the use of currency. crypto money Because there are things that are not regulated or do not fall within the scope of applicable regulations, countries are required to make their own decisions. There are countries that refuse, and there are also those that make special rules for this transaction.